The invisible killer - Santosa, Agus (MEDISAINS, 2020)
Viruses have been around for billions of years ago. They are everywhere, with varieties of shapes and sizes. They are microparasites with the ability to evolve and mutate. Some viruses can be so malignant and cause an outbreak that kills hundreds, and even millions, of people. What the world recently faces is one of those malignant viruses.